Drinking Water Platform System Design (OTODRINK) - Muhamad Fatchan; Dandy Firmansyah Putra; Agus Suwarno (Universitas Ibn Khaldun Bogor, 2023)
This research aims to address the issue of availability of safe drinking water in densely populated urban areas through the implementation of Internet of Things (IoT). The background of the study is based on the rapid population growth and its impact on the demand for water, as well as the increasing consumption of safe drinking water in society. The study utilizes the Otodrink system, which integrates ESP8266 microcontroller and RFID technology to distribute clean water automatically to user's tumblers. The research methodology includes system design, hardware and software development, and functional testing of the system. The findings indicate that the Otodrink system successfully distributes water efficiently and in a controlled manner, while reducing the use of plastic-packaged mineral water. The implications of this research are increased accessibility and availability of safe drinking water in urban areas, as well as a reduction in the negative environmental impact of plastic waste.